Evidence of a common cell origin in a case of pancreatic mixed intraductal papillary mucinous neoplasm–neuroendocrine tumor - Schiavo Lena, Marco; Cangi, Maria Giulia; Pecciarini, Lorenza; Francaviglia, Ilaria; Grassini, Greta; Maire, Renaud; Partelli, Stefano; Falconi, Massimo; Perren, Aurel; Doglioni, Claudio (Virchows Archiv : an international journal of pathology, 2021)
Recently, the term mixed neuroendocrine non-neuroendocrine neoplasms (MiNEN) has been proposed as an umbrella definition covering different possible combinations of mixed neuroendocrine-exocrine neoplasms. Among these, the adenoma plus neuroendocrine tumor (NET) combination is among the rarest and not formally recognized by the 2019 WHO Classification. In this setting, the debate between either collision tumors or true mixed neoplasms is still unsolved. In this report, a pancreatic intraductal papillary mucinous neoplasm (IPMN) plus a NET is described, and the molecular investigations showed the presence in both populations of the same KRAS, GNAS, and CDKN2A mutations and the amplification of the CCND1 gene. These data prove clonality and support a common origin of both components, therefore confirming the true mixed nature. For this reason, mixed neuroendocrine-exocrine neoplasms, in which the exocrine component is represented by a glandular precursor lesion (adenoma/IPMN) only, should be included into the MiNEN family.